Exploring the Genotype-Dependent Toolbox of Wheat under Drought Stress - Valya Vassileva; Mariyana Georgieva; Grigor Zehirov; Anna Dimitrova (Agriculture, 2023)
Drought stress imposes substantial constraints on the growth and production of wheat (Triticum aestivum L.), a globally important cereal crop essential for food security. To mitigate these adverse effects, researchers are intensifying their efforts to comprehend how different genotypes respond to drought stress, aiding in the development of sustainable breeding and management strategies. This review summarizes past and recent research on genotype-dependent responses of wheat plants to drought stress, encompassing morphological, physiological, biochemical, molecular, genetic, and epigenetic reactions. Screening drought-affected features at early developmental stages can provide valuable insights into the late growth stages that are closely linked to plant productivity. This review underscores the importance of identifying traits associated with drought resistance, and the potential of leveraging wheat diversity to select cultivars with desirable agronomic characteristics. It also highlights recent advancements in investigating Bulgarian wheat genotypes with varying levels of drought tolerance, specifically in detecting essential features contributing to drought tolerance. Cultivating drought-resistant wheat genotypes and understanding stress stability determinants could markedly contribute to enhancing wheat production and ensuring stable yields under changing climate conditions.